2022
DOI: 10.1063/5.0105540
|View full text |Cite
|
Sign up to set email alerts
|

Single-chain and condensed-state behavior of hnRNPA1 from molecular simulations

Abstract: Intrinsically disordered proteins (IDPs) are essential components for the formation of membraneless organelles, which play key functional and regulatory roles within biological systems. These complex assemblies form and dissolve spontaneously over time via liquid-liquid phase separation of IDPs. Mutations in their amino acid sequence can alter their phase behavior, which has been linked to the emergence of severe diseases. We study the conformation and phase behavior of a low-complexity domain of heterogeneous… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 81 publications
1
24
0
Order By: Relevance
“…We excluded pairs of residues that were separated by one or two bonds from the map because their contacts were primarily determined by the chain connectivity. The purpose of showing both the distance-based contact maps and energy maps is that they are complementary but distinct metrics, and using both is especially helpful for reliably determining contacts between residues of different sizes . As seen from Figures and S3, contacts were more evenly distributed along the chain contour for more uniformly charge-patterned sequences with nSCD ≲ 0.035 (EKV1 to EKV3).…”
Section: Results and Discussionmentioning
confidence: 99%
“…We excluded pairs of residues that were separated by one or two bonds from the map because their contacts were primarily determined by the chain connectivity. The purpose of showing both the distance-based contact maps and energy maps is that they are complementary but distinct metrics, and using both is especially helpful for reliably determining contacts between residues of different sizes . As seen from Figures and S3, contacts were more evenly distributed along the chain contour for more uniformly charge-patterned sequences with nSCD ≲ 0.035 (EKV1 to EKV3).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Membraneless organelles or biomolecular condensates formed through liquid – liquid phase separation (LLPS) have been widely reported in various cellular functions, including gene expression, signal transduction, stress response, and the assembly of macromolecular complexes. Examples of such condensates include the nucleolus, Cajal bodies, P bodies, and stress granules. Intrinsically disordered proteins (IDPs) play an important role in the formation of biomolecular condensates through LLPS. Due to the numerous similarities between IDPs and synthetic polymers, classical polymer models offer a powerful approach for investigating the conformations, dynamics, and phase behavior of IDPs. In particular, such models have been extensively used to reveal the sequence-dependent conformations of IDPs in solution and in condensates. …”
mentioning
confidence: 99%
“…14 These prior works suggest that principles from homopolymer theory can be applied with reasonable accuracy when attractive monomers are distributed rather uniformly along the protein sequence. 25 With these considerations, we investigated whether the similarity established at the single-chain level by scaling monomer interactions also leads to similarities in phase behavior for our model sequences having strong localized or weak distributed interactions. We performed direct coexistence simulations of the dilute and dense phases, computed time-averaged concentration profiles (Figure 4), and extracted the coexistence concentrations of the dilute and dense phases (Figure 5).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Despite these challenges, significant progress has been made in elucidating the sequence determinants of phase separation through experimental and computational studies. Among these studies, the work on the low-complexity domain (LCD) of hnRNPA1 , and the FUS prion-like domain have shown that the critical temperature T c and the saturation (dilute-phase) concentration c sat were altered when the number of aromatic residues (tyrosine) was varied. In addition, the mutation of arginine to lysine while maintaining the tyrosine content in FUS-like proteins led to a significant increase in c sat , thus implying a reduction in phase-separation propensity. , Further work on the FUS-LCD, using a combination of nuclear Overhauser experiments and all-atom molecular simulations, demonstrated that residues such as serine, glycine, and glutamine also play an important role in the stabilization of liquid-like condensates through interactions with other residues in the sequence. , Studies involving shuffling of charges in LAF-1 RGG and DDX4 have shown that charge patterning, frequently quantified by the sequence charge decoration parameter, influences the phase-separation propensity of a protein, highlighting the key role played by electrostatic interactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation